Improving the quality of training and fostering public officials in the Lao People’s Democratic Republic in the new era - Candidate Sengphaylin Chanthavisouk (Journal of State Management, 2024)
Training and fostering the contingent of public officials and civil servants is a critical task that plays a decisive role in enhancing the quality of human resources across all nations, including the Lao People's Democratic Republic. This article examines the current training and fostering activities for public officials and civil servants in the Lao People's Democratic Republic. Based on the achievements and the existing shortcomings, the article proposes several solutions to improve the quality of these activities in the new phase.